Penokohan Karakter Superhero Berhijab pada Webcomic Qahera dalam Memerangi Pemikiran Misoginis di Mesir - Yuani Asilady (Program Studi Magister Linguistik Terapan UNJ, 2022)
This article aims to analyze and elaborate the interpretation of the depiction of misogynistic cases that is contained in the web comic “Qahera the Superhero”. In this study, the researcher interprets the misogynistic issue which refers to the interview section from an Illustrator of “Qahera the Superhero” named Deena, the results of the interview was later published on the vice.com page. This article is a descriptive qualitative research, in which the research conducted data searches regarding to the explanation and description of misoginism, especially for what is happening in Egypt. The method of this research is a literature review which using journals that is related to the issues that is relevant to this study. In addition, the researchers made observations and searches about the news that was published on the vice.com page with the title “Qahera, Karakter Superhero Berhijab asal Mesir Membasmi Pemikiran Misoginis”. The results of the study found that the misogynistic issues contained in the Qahera comic were the result of visualization of cases of sexual harassment and violence that occurred in Egypt. The characterization of the hijab-wearing superhero Qahera is a picture of Muslim women who experience violence and they rise up to be able to voice the injustices they experience.